Antiproliferative Scalarane-Based Metabolites from the Red Sea Sponge Hyrtios erectus - Elhady, Sameh S. (Mar Drugs, 2016)
Two new sesterterpenes analogs, namely, 12-acetoxy,16-epi-hyrtiolide (1) and 12β-acetoxy,16β-methoxy,20α-hydroxy-17-scalaren-19,20-olide (2), containing a scalarane-based framework along with seven previously reported scalarane-type sesterterpenes (3–9) have been isolated from the sponge Hyrtios erectus (order Dictyoceratida) collected from the Red Sea, Egypt. The structures of the isolated compounds were elucidated on the basis of their spectroscopic data and comparison with reported NMR data. Compounds 1–9 exhibited considerable antiproliferative activity against breast adenocarcinoma (MCF-7), colorectal carcinoma (HCT-116) and hepatocellular carcinoma cells (HepG2). Compounds 3, 5 and 9 were selected for subsequent investigations regarding their mechanism of cell death induction (differential apoptosis/necrosis assessment) and their influence on cell cycle distribution.